PENERAPAN STRATEGI CELEBRITY ENDORSEMENT UNTUK MEMBANGUN BRAND AWARENESS PADA MASA PANDEMI COVID-19 DI BALI ZOO - Sagung Mas Suryaniadi; Ni Nyoman Supiatni; Ni Made Wiwik Purnamiasih (Forum Manajemen, 2022)
The Covid-19 pandemic has had an impact on various tourism sectors in Bali. The drastic decline in the number of visitors and changes in the target market from foreign tourists to local and domestic tourists was experienced by Bali Zoo. Bali Zoo should adapt to various aspects of the company, including the promotion strategy. This study aims to determine the implementation of the Celebrity Endorsement strategy carried out by Bali Zoo in an effort to get brand awareness during the Covid-19 pandemic, including the selection procedure and content presentation in the Celebrity Endorsement strategy. The research method used is qualitative descriptive analysis techniques. The results of the study indicate that the Celebrity Endorsement strategy can be an effective promotional strategy during the pandemic which is carried out by barter collaboration. The success of implementing this strategy can be seen from the level of social media engagement of Bali Zoo. The procedure for selecting celebrity endorsers at Bali Zoo goes through several stages, namely: searching, screening, inviting, negotiation, arrival of celebrity endorsers, and content uploaded by celebrity endorsers. Content presentation is carried out by celebrity endorsers usually include photos or videos, tag Bali Zoo accounts and locations, include caption and hashtag.